The technical preparation of the young rowers of Pinar del Río - Luis Enrique Herrera Flores; Yolainy Govea Díaz; Yudelqui Martínez León (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2020)
The technical preparation as one of the components of the sport preparation in rowing has a great importance because of the relationship with the competitive result. During the technical preparation of the rowers, juvenile category of Pinar del Río, deficiencies have been detected in the execution of the rowing technique, in each of its phases. That is why, for this study, the objective was to characterize the technical preparation of the juvenile male category rowers of the EIDE "Ormani Arenado" of Pinar del Río. The population used was composed of nine athletes of the juvenile category and six coaches, including the one who leads the preparation of this team mentioned above. For the development of this research, theoretical and empirical methods were used. Among the theoretical methods are systemic-structural-functional, historical-logical, analysis-synthesis, induction-deduction. The empirical methods used were document analysis, observation, interview and survey. The use of these methods made it easier for the researcher to know the real state of the technical preparation of these athletes and showed deficiencies such as execution errors, the non-existence of tests to evaluate the technique, it is not planned or controlled taking into account the individual characteristics of the athletes; however, it is considered by the coaches, as an aspect of great importance, the technical preparation in this sport.